THE EFFECT OF READING ROMANCE NOVEL MEDIA ON STUDENTS READING ABILITY OF CLASS XI IPS AT SMA NEGERI 3 KUTACANE IN THE ACADEMIC YEAR 2023-20242023/2024 - SalihinSalihin; Edi Syahputra; Wikiaprian Pinim (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
A Thesis English Education Department the Faculty of Teachers Training and Education, stkip us Kutacane.The aim of the research was to find out whether the use romance novel media has a significance effect in reading abilities. Population used in this study of class XI were 128 and samples used in this study were 23 students. The method used in this study is an experimental method with a one group as test design .This study was carried on using quantitate method. The data was analysed by using t-test. The researcher found the test mean = 79,35 , deviation standard = 3,70 deviation error = 0,79. From this analysis, researcher found that guided romance novel media has significance in teaching reading. with the mode obtained being a value of 80 which was the most obtained by 10 students in class XI IPS 2. Based on the data from the test results on the ability to increase reading and if it is related to the KKM score for English subjects for senior high school = 75. So the reading romance novel media on students reading ability is included in the good category. Thus, from the results of the hypothesis testing above, it can be concluded that there is the The Effect of Reading Romance Novel Media on Students Reading Ability of Class XI IPS at SMA Negeri 3 Kutacane in The Academic Year 2023/2024.